Use of an Extensile Posterior Approach to the Elbow Joint: Early Results of the Anconeus Approach. Issue 8 (August 2020) - Landrum, Matthew; Sager, Brian; Youngman, Tyler; Green, Adam; Sathy, Ashoke; Starr, Adam; Sanders, Drew
Abstract : Summary: Commonly used surgical approaches to the elbow typically limit the surgeon to either medial or lateral exposure, can provide visualization limited by an intact radial head, and may not be extensile. We describe the use of a well recognized, but uncommonly used, extensile approach to the medial and lateral compartments of the elbow joint. This approach provides access to address pathology of the proximal radius, ulna, and the distal humerus and can be made extensile both proximally and distally. The anconeus approach is easy to perform and well tolerated by patients. A retrospective review of 42 patients is included. Abstract : Supplemental Digital Content is Available in the Text.